Honey, an unexplored topical wound dressing agent in Nigerian veterinary practice (2016)
This paper presents an overview of honey as a wound dressing agent, its mechanism of action, selected cases of wounds managed with honey and a survey of veterinarians’ perception and usage of honey for wound management in Nigeria. Structured questionnaires were administered to veterinary practitioners predominantly in Southwest Nigeria to evaluate their awareness, usage and concerns about honey as a wound dressing agent. Case reports of animal patients’ wounds managed with honey are presented in a logical fashion to showcase honey efficacy in wound management. There was remarkable healing with honey in the cases managed. Many of the respondents did not consider honey as first choice in wound management and availability of pure honey is a major concern expressed with honey use. More veterinarians in Nigeria should use honey for its high efficacy and cost effectiveness in the management of animal wounds